The Influence of Suppliers, Knowledge Transfer on the Performance of the MSME Fashion Supply Chain through Sustainable Procurement - Fadhilah Insani Liesvy Turrina; Nasar Buntu Laulita (Universitas KH. Abdul Chalim Mojokerto, 2026)
The fashion industry, especially fashion MSMEs, has an important role in the economy but faces various challenges in supply chain management, such as dependence on suppliers, limited knowledge transfer, and low implementation of sustainable procurement. The complexity of the supply chain network and the lack of understanding of sustainability practices cause the performance of the MSME supply chain to be suboptimal. This study aims to analyze the influence of suppliers and knowledge transfer on the performance of the fashion MSME supply chain with sustainable procurement as a mediating variable. The research method used is a quantitative approach with data collection through questionnaires distributed to fashion MSME actors. Data were analyzed using statistical analysis methods to test the relationships between variables in the research model. The results show that suppliers and knowledge transfer have a positive effect on sustainable procurement and supply chain performance. In addition, sustainable procurement has been proven to mediate the relationship between suppliers and knowledge transfer on the performance of the fashion MSME supply chain. These findings indicate that strengthening relationships with suppliers and increasing knowledge transfer can support the implementation of sustainable procurement as well as improve supply chain performance. This study recommends that fashion MSMEs increase collaboration with suppliers, strengthen the knowledge sharing process, and develop an understanding of sustainability practices to improve the competitiveness and sustainability of their businesses in the future.